2012
DOI: 10.1159/000339857
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Secretion from Human Monocytes Potentiated by P-Selectin-Mediated Cell Adhesion

Abstract: Background/Aim: P-selectin is a carbohydrate-recognizing cell adhesion molecule expressed on activated platelets and endothelial cells. It plays a crucial role in the recruitment of leukocytes to inflammatory and hemorrhagic sites. Cell adhesion mediated by P-selectin induces leukocyte activation, such as the generation of reactive oxygen species and the expression of blood coagulation factors. We assessed how P-selectin-mediated cell adhesion affects cytokine secretion from monocytes. Methods: Human periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 54 publications
4
33
0
2
Order By: Relevance
“…32 Additionally, monocyte adhesion to platelets resulted in the release of cytokines, thereby further promoting an inflammatory phenotype. 33 Our present data, showing increased CD11b expression and L-selectin shedding on both monocytes and neutrophils after rolling over the FLIPRs, are in accordance with these studies. Furthermore, other studies have shown that platelets are able to induce a proinflammatory phenotype on monocytes and neutrophils on complex formation, resulting in increased adhesive properties toward endothelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…32 Additionally, monocyte adhesion to platelets resulted in the release of cytokines, thereby further promoting an inflammatory phenotype. 33 Our present data, showing increased CD11b expression and L-selectin shedding on both monocytes and neutrophils after rolling over the FLIPRs, are in accordance with these studies. Furthermore, other studies have shown that platelets are able to induce a proinflammatory phenotype on monocytes and neutrophils on complex formation, resulting in increased adhesive properties toward endothelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…CD62P-PSGL-1 binding as well as platelet release of CCL5 and tumour necrosis factor superfamily member 14 (TNFSF14) induce monocyte expression of monocyte chemotactic protein 1 (MCP-1), TNF-α, IL-1β, IL-6, IL-8, IL-12 and macrophage inflammatory protein 1β (MIP-1β) in vitro [56,60,61].…”
Section: Pro-inflammatory Cytokine Expressionmentioning
confidence: 99%
“…THP-1 human monocytes and mouse WEHI-274.1 monocytes were obtained from ATCC and were grown in RPMI-1640 medium or DMEM, respectively, containing 10% FCS and 0.05 mM 2-ME, as instructed by the supplier. FIHM were isolated from peripheral blood of healthy donors using Ficoll hydraplaque [16], and monocytes were enriched and verified using flow cytometer, as described previously [17].…”
Section: Cell Culturementioning
confidence: 99%